(untitled) (Research, Society and Development, 2021)
The hydrological cycle, affected by climate change caused by the process of development and industrialization, has received great attention from the scientific community around the world, and with this, many studies have been carried out to show that changes in precipitation are becoming evident on a scale global. In addition, extreme events such as prolonged droughts, floods and landslides have caused social and environmental impacts in large urban areas, with flooding in highly waterproof surfaces being the most frequent ones, due to insufficient infrastructure in drainage systems. Therefore, this work aimed to analyze the trend in time series of the Standardized Precipitation Index (SPI) for the time scales of 1, 3, 6, 12, 24 and 48 months, using the Mann-Kendall test at the level 5% significance level. For this purpose, monthly precipitation data from the conventional meteorological station Recife (Curado), located in the state of Pernambuco, Brazil, between the period 1962 to 2019 were used. The results showed that for the time scales of 1 and 3 months there is no significant temporal trend, while significant negative trends were obtained for the other scales, which indicated an increase in drought severity. In relation to the frequencies of occurrences, an increase in the occurrence of dry periods is observed for long-term conditions (SPI-12, SPI-24 and SPI-48) and for wet periods an increase was observed only in the moderately humid category.